Celebrating Adam Watkins' 10th Birthday at Home - Watkins, Howard::::::::: (1988)
Adam Watkins, Josiah Gordon, ?, Art Wille, ?, Gregory Leifer, and ? Seated at dining table eating ; seated at counter; Jared Gordon, Devon Bleile-Kratzer, and Seth Tilley